Financial Behavior dan Financial Knowledge Terhadap Keputusan Pembayaran Dana Pensiun pada Aparatur Sipil Negara di Provinsi Gorontalo - Hais Dama; Yayu Isyana Pongoliu; Sulistiawati Adam (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
The research analyze how the level of financial knowledge and financial behavior affects the decision of choosing fully funded or pay as yo go pensiun fund for Civil Servant in Gorontalo Province. The pension fund have a huge portion in Government budget so the new scheme of retirement plan is introduced to minimize the risk of asymmetric government budget and the rising of old age peope in civil servant. The data consist of 200 samples from the civil servants around Gorontalo Province. The data analysis technique using logistic regression. Our result show evidence that group of samples that have a higher degree in financial knowledge and financial behavior tend to choose fully funded pension scheme. This is consistent with our previous hypothesis that the higher financial literacy lead to good skill to manage personal finance include retirement plan and investment.